FORMULASI DAN UJI SUN PROTECTION FACTOR (SPF) SEDIAAN KRIM EKSTRAK ETANOL 96% DAGING BUAH LABU SIAM (Sechium edule (Jacq.) Sw.) SECARA IN VITRO - Annajim Daskar; Debby Heldayani; Eva Nurul Baity (Journal of Innovative and Creativity, 2025)
Excessive exposure to ultraviolet (UV) rays can cause various damage to the skin, such as premature aging and skin cancer. The use of natural sunscreens is a safe and environmentally friendly alternative. Chayote (Sechium edule (Jacq.) Sw.) is known to contain active compounds such as flavonoids and phenolics that have the potential as photoprotective agents. This study aims to formulate a cream preparation of 96% ethanol extract of chayote flesh and evaluate its physical characteristics and Sun Protection Factor (SPF) value in vitro. This study used an experimental method. The flesh of chayote (Sechium edule (Jacq.) Sw.) was extracted using the maceration method, followed by the development of a topical cream formula and measurement of the Sun Protection Factor (SPF) value in vitro using. Based on the results of physical characteristic tests, all formulas showed compliance with the criteria for good cream quality, except in the protection power test, where reddish spots were observed in formula F2, and in the physical stability test, emulsion phase separation was found. The SPF value increased with increasing extract concentration. Formula F1 showed an SPF of 15.88; F2 16.68; and F3 18.52, categorized as moderate to high protection. Therefore, chayote pulp extract cream has the potential to be a safe and effective natural sunscreen. It can be concluded that the chayote pulp extract cream preparation has the potential to be used as a natural sunscreen.